In Vitro Antibacterial Activity of Black Soldier Fly (Hermetia Illucens) Larva Extracts Against Gram-Negative Bacteria - Harlystiarini Harlystiarini; Rita Mutia; I Wayan Teguh Wibawan; Dewi Apri Astuti (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
The aim of this study was to evaluate the in vitro antibacterial activity of Black soldier fly (BSF) larva extract. The BSF larva was extracted using methanol and then tested for antibacterial activity using agar diffusion method (zone growth inhibition). The antibacterial activity was conducted against Salmonella sp. and Escherichia coli, two important bacterial strains in poultry, using six dilution levels (10 mg/ml, 20 mg/ml, 40 mg/ml, 80 mg/ml, 160 mg/ml and 320 mg/ml). All the results were subjected analyze using t-test method. Based on the diameter of the inhibition zone, the BSF larva extract has a strong (P<0.05) antibacterial activity against Salmonella sp. and E. coli when the concentration used 320 mg/ml. In addition, BSF larva extract also contain high amount of lauric acid (49.18%), a saturated fatty acid that has been proven to proposes as antibacterial agent. Therefore, it could be concluded that the BSF larva extract could be used as a candidate for antibacterial substances.